EFEKTIVITAS PIJAT TUINA UNTUK MENINGKATKAN BERAT BADAN BALITA USIA 1-5 TAHUN - Melia Rahma; Ririn Anggraini; Fera Tri Kurniawan (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
Growth disorders can increase the risk of malnutrition; the World Health Organization (WHO) reported that the prevalence of malnutrition in the world has increased from 17.6% in 2015 to 25.0% in 2020. Government efforts to prevent nutritional problems in toddlers strart from pregnancy time to todfletjood itself, such as giving 90 tablets of Fe tablets during pregnancy. Growth stimulation requires efforts to handle nutritional problems in toddlers, which can be done by non-pharmacological methods. It is called acupuncture/herbal massage. One therapy to overcome the problem of weight gain is tuina massage. This study aims to determine the effectiveness of tuina massage to increase the weight of toddlers aged 1-5 years. This study used the literature study method, so an analysis of the results of the search for journals and articles with a theoretical review of 10 journals and 2 books has been reviewed. The results of this study were how to do tuina massage, the most effective massage is using 8 movements with massage techniques sliding, massaging, friction, pulling, rotating, shaking and moving certain points. This, it would affect the flow of body energy by holding and pressing certain parts of the body. The effective tuina massage frequency is once a day for at least 15 minutes using 8 movements for 6 consecutive days. Tuina massage is effective for increasing the weight of toddlers aged 1-5 years, and there is effectiveness before and after doing tuina massage to increase the weight of toddlers aged 1-5 years. From the literature review, it is concluded that tuina massage is effective in increasing the weight of toddlers. This can be used as an alternative for toddlers aged 1-5 years who have problems gaining weight.